Interplay between Trx‐1 and S100P promotes colorectal cancer cell epithelial–mesenchymal transition by up‐regulating S100A4 through AKT activation. Issue 4 (31st January 2018) - Zuo, Zhigui; Zhang, Peili; Lin, Feiyan; Shang, Wenjing; Bi, Ruichun; Lu, Fengying; Wu, Jianbo; Jiang, Lei
Abstract: We previously reported a novel positive feedback loop between thioredoxin‐1 (Trx‐1) and S100P, which promotes the invasion and metastasis of colorectal cancer (CRC). However, the underlying molecular mechanisms remain poorly understood. In this study, we examined the roles of Trx‐1 and S100P in CRC epithelial‐to‐mesenchymal transition (EMT) and their underlying mechanisms. We observed that knockdown of Trx‐1 or S100P in SW620 cells inhibited EMT, whereas overexpression of Trx‐1 or S100P in SW480 cells promoted EMT. Importantly, S100A4 and the phosphorylation of AKT were identified as potential downstream targets of Trx‐1 and S100P in CRC cells. Silencing S100A4 or inhibition of AKT phosphorylation eliminated S100P‐ or Trx‐1‐mediated CRC cell EMT, migration and invasion. Moreover, inhibition of AKT activity reversed S100P‐ or Trx‐1‐induced S100A4 expression. The expression of S100A4 was higher in human CRC tissues compared with their normal counterpart tissues and was significantly correlated with lymph node metastasis and poor survival. The overexpression of S100A4 protein was also positively correlated with S100P or Trx‐1 protein overexpression in our cohort of CRC tissues. In addition, overexpression of S100P reversed the Trx‐1 knockdown‐induced inhibition of S100A4 expression, EMT and migration and invasion in SW620 cells. The data suggest that interplay between Trx‐1 and S100P promoted CRC EMT as well as migration and invasion by up‐regulating S100A4 through AKT activation, thus providing further potential therapeutic targets for suppressing the EMT in metastatic CRC.